Improvement of sub region matching illumination transfer in hybrid shadow removal method for moving vehicle video - Setiyono, Budi; Ratna Sulistyaningrum, Dwi; ., Soetrisno; Al-Habib, Hasanuddin (International Journal of Engineering and Technology, 2018)
Intelligent Transportation System (ITS) is a concept to manage transportation based on technology development. Video from surveillance cameras can be used for monitoring the number of vehicles and speed using digital image processing. Shadows on the vehicle is one of the noise that must be removed in order to obtain better accuracy. Shadow is caused by the reflection of objects exposed to the light. In this study, we combined two methods to eliminate shadows on moving vehicle, the subregion illumination transfer method and the background-based Gaussian mixture model. Foreground image is used for sub-Region Illumination Transfer and gamma decoding processes is used to detect the presence of shadows The detected shadow is removed by replacing it with the background in that position. Experiments are done by making simulated video of moving objects without shadows and objects that have a shadow. By using the proposed method, the shadow will be omitted, and the results are compared with the object without the shadow. The experimental results are: mean value of PSNR for objects moving closer to the camera with a light intensity of 0.8 is 53.47. While on the moving object with a small shadow area, we obtained an average PSNR of 51.87927dB.
Keywords: Shadow Removal; Gaussian Mixture Model; Gamma-Decoding Method; Intelligent Transportation System; Moving Object.